A mid-twentieth-century Anthropocene makes the Holocene more important than ever. (April 2016) - Braje, Todd J.
Abstract : I thank all the authors for their thoughtful responses to my paper. I believe they effectively highlight some of the diverse opinions about the concept of the Anthropocene and underscore the challenges faced by the ICS subcommission.